2021
DOI: 10.25159/2520-5293/8647
|View full text |Cite
|
Sign up to set email alerts
|

Talent Management and its Impact on Innovative Work Behaviour among Registered Nurses in Public Hospitals of Malawi

Abstract: The Malawi government established and implemented various talent management practices within public hospitals in the country to enhance accessibility, productivity and energy of its health personnel, and to boost the quality of health service delivery. Innovative work behaviours such as the creation, introduction and application of new ideas are key to achieving productivity, accessibility and energy of health personnel. The sure way of achieving innovative work behaviour is through the implementation of talen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that the demand for talented employments in the coming years is going to increase, while the supply will drop. There is no doubt that technology and globalization have changed our lives, as they have led to increased competition on talent (9) . Thus, the potential growth of organizations worldwide depends on the ability of organizations to ensure that the right people with the right skills are in the right place at the right time, and focused on the right activities.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the demand for talented employments in the coming years is going to increase, while the supply will drop. There is no doubt that technology and globalization have changed our lives, as they have led to increased competition on talent (9) . Thus, the potential growth of organizations worldwide depends on the ability of organizations to ensure that the right people with the right skills are in the right place at the right time, and focused on the right activities.…”
Section: Introductionmentioning
confidence: 99%